Ngaben Massal di Desa Panji Kabupaten Buleleng Dalam Perspektif Manajemen George R. Terry - Sedana, I Made (Jurnal Penelitian Agama Hindu, 2024)
Ngaben ceremony is a ceremony carried out with large funds and involves many people. To be carried out properly, the management aspect is very crucial. This study aims to describe Mass ngaben from a management perspective. Thus, it can be identified which parts are in accordance with management theory and which parts need to be improved. The data collection in this study was conducted by using interview, observation, and documentation techniques. The data obtained were analyzed qualitatively using an interactive data analysis model consisting of three stages, data reduction, data display, and conclusion drawing/verification. The results of this study found that the ngaben ceremony was carried out using management principles according to George R. Terry's theory which included four stages, namely planning, organizing, actualizing, and controlling. In the implementation of these management principles, the Balinese do it based on two general concepts, namely yadnya and ngayah. In other words, the Balinese view the ngaben ceremony as a form of sacred sacrifice and they are obliged to carry it out sincerely, i.e. selflessly and not expecting anything in return.